2014
DOI: 10.1371/journal.pone.0108359
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction between Neuroanatomical and Psychological Changes after Mindfulness-Based Training

Abstract: Several cross-sectional studies have documented neuroanatomical changes in individuals with a long history of meditation, while a few evidences are available about the interaction between neuroanatomical and psychological changes even during brief exposure to meditation. Here we analyzed several morphometric indexes at both cortical and subcortical brain level, as well as multiple psychological dimensions, before and after a brief -8 weeks- Mindfulness Based Stress Reduction (MBSR) training program, in a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 58 publications
7
55
0
2
Order By: Relevance
“…In fact, the only one of the four studies included in this review to measure trait mindfulness37 reported no significant change in mindfulness as a result of the intervention, a surprising finding that runs counter to other evidence 24. The authors attribute this result to the use of the MAAS 39.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 60%
See 3 more Smart Citations
“…In fact, the only one of the four studies included in this review to measure trait mindfulness37 reported no significant change in mindfulness as a result of the intervention, a surprising finding that runs counter to other evidence 24. The authors attribute this result to the use of the MAAS 39.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 60%
“…Two studies compared mindfulness-based interventions based on the MBSR programme, delivered over 8 weeks37 and 10 weeks,36 with wait-list. A third study tested a bespoke mindfulness-based programme of contemplative mental training delivered in three different 3-month modules 35.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, greater insular thickness has been noted among meditators, 73 and a course of MBSR was associated with increased insular thickness and reduced alexithymia in meditation-naive individuals. 74 Thus, via restoration of insular functioning, mindfulness-based approaches may be beneficial in improving body awareness and awareness of emotions, abilities that are often compromised in those with PTSD [75][76][77] and are associated with emotional overmodulation. 7,63 Emerging work has also noted neurobiological changes following a course of mindfulness-based exposure therapy (MBET) among individuals with PTSD.…”
Section: Prefrontal Modulation Of Limbic Structures and Mindfulnessmentioning
confidence: 99%